Somatic embryogenesis response in Argentinian sugarcane genotypes for in vitro mutagenesis application - Di Pauli, Valentina (2019)
XXX Congress of the ISSCT (International Society of Sugar Cane Technologists), Tucumán, from 31 August to 8 September 2019